2016
DOI: 10.1007/s00280-016-3089-4
|View full text |Cite
|
Sign up to set email alerts
|

TACTIC: a multicentre, open-label, single-arm phase II trial of panitumumab, cisplatin, and gemcitabine in biliary tract cancer

Abstract: A marker-driven approach to patient selection was feasible in advanced biliary tract cancer in an Australian population. The combination of panitumumab, gemcitabine, and cisplatin in KRAS wild-type cancers was generally well tolerated and showed promising clinical efficacy. Further exploration of anti-EGFR therapy in a more selected population is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…(76) KRAS mutations are known to preclude any therapeutic benefit from anti-EGFR therapies in other cancers, but only two studies have suggested this effect in CCA for erlotinib and panitumumab. (77,78) The recent development of a patientderived xenograft model of iCCA bearing the most frequent KRAS mutation (G12D) should provide answers on the role of this mutation in anti-EGFR treatment efficacy. (68) Secondary resistance appears under long-term anti-EGFR treatment.…”
Section: Resistance Mechanisms To Anti-erbb Therapiesmentioning
confidence: 99%
“…(76) KRAS mutations are known to preclude any therapeutic benefit from anti-EGFR therapies in other cancers, but only two studies have suggested this effect in CCA for erlotinib and panitumumab. (77,78) The recent development of a patientderived xenograft model of iCCA bearing the most frequent KRAS mutation (G12D) should provide answers on the role of this mutation in anti-EGFR treatment efficacy. (68) Secondary resistance appears under long-term anti-EGFR treatment.…”
Section: Resistance Mechanisms To Anti-erbb Therapiesmentioning
confidence: 99%
“…A recent phase II trial stratified BTC patients based on KRAS status, but failed to demonstrate that KRAS status predicted the population most likely to benefit from anti-EGFR therapy (45). Furthermore, two biomarker-driven trials that was restricted to KRAS wild-type patients failed to show a clinically significant improvement in PFS or OS using panitumumab combined with chemotherapy (46,47). These studies call into question the utility of KRAS status as a clinically relevant biomarker predictive of EGFR therapy response in BTC, as opposed to colon cancer.…”
Section: Egfrmentioning
confidence: 99%
“…These studies call into question the utility of KRAS status as a clinically relevant biomarker predictive of EGFR therapy response in BTC, as opposed to colon cancer. The relative importance of mutations in other EGFR pathway genes, such as BRAF, are being investigated as mechanisms of resistance to anti-EGFR agents (47,48).…”
Section: Egfrmentioning
confidence: 99%
“…There have been a couple of attempts at targeting EGFR in cholangiocarcinoma with monoclonal antibodies instead of EGFR tyrosine kinase inhibitors. One such study (BINGO trial) did not show meaningful improvement in survival with cetuximab in combination with gemcitabine and cisplatin as compared to a placebo in cholangiocarcinoma patients, however, a more recent single arm trial (TACTIC trial) that included only KRAS wild type patients showed a response rate of 46% suggesting a more selected population as a better target . We did not include HER1/EGFR expression analysis, however, studies performed with erlotinib prior to our study showed higher EGFR expression in BDC and HCC patients without correlation with erlotinib responsiveness and the study by Lee et al.…”
Section: Discussionmentioning
confidence: 84%